Heterologous Platelet-Rich Plasma in the Treatment of Severe Skin Damage - Cristina Vocca; Francesco Romano; Gianmarco Marcianò; Vincenzo Cianconi; Davida Mirra; Andrea Dominijanni; Giovambattista De Sarro; Luca Gallelli (Reports, 2023)
Accidental soft tissue injuries are a frequent injury. Platelet-rich plasma (PRP) is an interesting therapeutic option for wounds and skin damage. In this case report, we describe a 37-year-old man that presented to our ward of pain medicine for an accidental severe leg injury associated with skin and soft tissue loss, with severe pain and poor sensation. History revealed the use of recreational drugs without viral infections or systemic diseases. Wound debridement, wound dressings, systemic antibiotics (amoxicillin 1000 mg tid and azithromycin 500 mg od), and non-steroidal anti-inflammatory drugs (ibuprofen 600 mg bid) reduced pain but did not improve the skin and soft tissue. A fibrin membrane with concentrated growth factors was applied, yielding an improvement in the injury in 16 months without the need for skin grafting.